2013
DOI: 10.4081/aiua.2013.4.157
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells in blood and urine samples from bladder cancer patients undergoing BCG immunotherapy

Abstract: Objectives: Immunotherapy with BCG (Bacille Calmette-Guérin) after transurethral resection of the bladder tumor represents a highly effective primary treatment for intermediate and high-risk superficial bladder cancer. The effectiveness of this therapy has been documented, but its mechanism of action is not clear yet. In the present study, we investigated the changes of dendritic cells (DC) numbers in peripheral blood and urine of patients with superficial bladder cancer undergoing BCG intravescical therapy Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…BC is a major urinary malignancy around the world ( 19 , 20 ). It is reported that chromosomal anomalies, genetic polymorphisms, and genetic and epigenetic alterations may contribute to the tumorigenesis and progression of BC ( 21 ). Therefore, the early detection of BC is important.…”
Section: Discussionmentioning
confidence: 99%
“…BC is a major urinary malignancy around the world ( 19 , 20 ). It is reported that chromosomal anomalies, genetic polymorphisms, and genetic and epigenetic alterations may contribute to the tumorigenesis and progression of BC ( 21 ). Therefore, the early detection of BC is important.…”
Section: Discussionmentioning
confidence: 99%
“…In general, although with some level of heterogeneity, circulating pDCs are decreased in human cancer patients compared to healthy donors, particularly in advanced stage diseases, with a single relevant exception in a study of non-small-cell lung cancer (NSCLC) [144]. Specifically, the peripheral blood pDCs resulted decreased in cohort studies from ovarian cancer [137], NSCLC [145], bladder cancer [146], CRC [147] and advanced breast cancer patients [148]. Notably, in ovarian cancer, circulating pDCs are partially restored after complete remission by chemotherapy [137].…”
Section: Clinical Significance Of the Pdcs Compartment In Human Cancementioning
confidence: 99%
“…Our results showed that CSC-DC vaccination conferred host CSC-specific CTL activity and antibody responses, resulting in significantly reduced population of ALDH(high) CSCs in treated tumours[ 14 ]. In addition, new vaccine adjuvants for cancer immunotherapy are being actively developed as an effort to augment vaccine-induced immune response against tumour-specific antigens in several studies[ 15 17 ]. Investigation and application of novel adjuvant may enhance the therapeutic efficacy of CSC-DC vaccine.…”
Section: Short Communicationmentioning
confidence: 99%